2013
DOI: 10.3818/jrp.15.1.2013.67
|View full text |Cite
|
Sign up to set email alerts
|

Creation and Validation of the Ohio Youth Assessment System (OYAS) and Strategies for Successful Implementation

Abstract: As Ohio began to address the gaps in delivering effective juvenile justice programming in the state, it recognized that a statewide risk assessment system was needed. The Department of Youth Services (DYS) explored its options and determined that the best course of action was to develop a risk assessment prospectively to address the needs of youth across multiple stages of the juvenile justice system. DYS partnered with the University of Cincinnati Center for Criminal Justice Research (CCJR) to develop the Ohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 2 publications
0
26
0
Order By: Relevance
“…Presently, the OYAS has been adopted and adapted by juvenile jurisdictions in Indiana, Kentucky, Arizona, Texas, and California. The OYAS-DIS is administered to youth offenders after they have been adjudicated by a juvenile court (Lovins & Latessa, 2013). To assess the risk of recidivism, it uses a mix of empirically validated static and dynamic risk and need factors that can be used to match each youth to individually appropriate interventions.…”
Section: The Oyasmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, the OYAS has been adopted and adapted by juvenile jurisdictions in Indiana, Kentucky, Arizona, Texas, and California. The OYAS-DIS is administered to youth offenders after they have been adjudicated by a juvenile court (Lovins & Latessa, 2013). To assess the risk of recidivism, it uses a mix of empirically validated static and dynamic risk and need factors that can be used to match each youth to individually appropriate interventions.…”
Section: The Oyasmentioning
confidence: 99%
“…There is some promising research on the predictive validity of the OYAS-DIS based on some initial validation studies (Lovins & Latessa, 2013). Further, a revalidation of the OYAS-DIS found that the tool can predict recidivism moderately well across different types of samples and counties (McCafferty, 2013, 2016).…”
Section: The Oyasmentioning
confidence: 99%
“…So far, research on the OYAS‐Disposition Tool has produced results that show support for the validity of the tool and that its ability to predict general recidivism is in line with other well‐performing tools. For example, in two studies in which the OYAS‐Disposition Tool was examined, scholars found that the total score of the tool correlates with recidivism at a level between r = .30 and .32 (Lovins & Latessa, ; McCafferty, ). Unpublished validity research results also show that this tool is as predictive of recidivism (Latessa et al., ; Latessa, Lovins, & Lux, ) as other commonly used youth risk assessments, such as the YLS/CMI (Schwalbe, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One tool that was designed for general use across a diverse offender population is the Ohio Youth Assessment System‐Disposition Tool (OYAS‐Disposition Tool; Latessa, Lovins, & Ostrowski, ). Although scholars have yet to examine the efficacy of this tool with sex offenders, it is still widely used for this purpose, such as statewide in several locations (e.g., Ohio, Arizona, Texas, and Indiana) and by numerous other county‐level jurisdictions around the United States (Latessa et al., ; Lovins & Latessa, ; McCafferty, ).…”
mentioning
confidence: 99%
“…The measure of cumulative risk included 17 items tapping a number of previously identified risk and needs domains (see Baglivio, 2009;Latessa, Lovins, & Ostrowski, 2009;Lovins & Latessa, 2013;Newsome & Sullivan, 2014). The domains included in the measurement process include family attachment and parental monitoring; substance use (both recent and early onset); antisocial peer association; social support; school attachment and performance; and prosocial skills and activities.…”
Section: Cumulative Risk Scorementioning
confidence: 99%